2022
DOI: 10.3390/ijms23031721
|View full text |Cite
|
Sign up to set email alerts
|

Growth Repressor GmRAV Binds to the GmGA3ox Promoter to Negatively Regulate Plant Height Development in Soybean

Abstract: Plant height is an important component of plant architecture, and significantly affects crop quality and yield. A soybean GmRAV (Related to ABI3/VP1) transcription factor containing both AP2 and B3 domains is a growth repressor. Three GmRAV-overexpressing (GmRAV-ox) transgenic lines displayed extremely shorter height and shortened internodes compared with control plants, whereas transgenic inhibition of GmRAV expression resulted in increased plant height. GmRAV-ox soybean plants showed a low active gibberellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Without further research to understand the impact of each identified candidate gene individually, it is difficult to model what is likely to be complex interactions of these genes in relation to photoperiod response. Recent work established a regulatory link between the GmTEM1a ortholog, GmTEM1b (GmRAV), and several gibberellins-associated genes in the modulation of plant height in soybean (Xue et al, 2022). It would be interesting to investigate whether there is a similar link between the GmTEM1a, GmGA2OX5, and GmGA2OX6 genes identified in this study in the control of flowering.…”
Section: Future Researchmentioning
confidence: 74%
“…Without further research to understand the impact of each identified candidate gene individually, it is difficult to model what is likely to be complex interactions of these genes in relation to photoperiod response. Recent work established a regulatory link between the GmTEM1a ortholog, GmTEM1b (GmRAV), and several gibberellins-associated genes in the modulation of plant height in soybean (Xue et al, 2022). It would be interesting to investigate whether there is a similar link between the GmTEM1a, GmGA2OX5, and GmGA2OX6 genes identified in this study in the control of flowering.…”
Section: Future Researchmentioning
confidence: 74%
“…A few mutants of the AP2 genes have been reported as candidate genes of dwarf plants, such as ddf1 in Arabidopsis ( Magome et al., 2004 ), ndl1 in rice ( Kusnandar et al., 2022 ), and dil1 in maize ( Jiang et al., 2012 ). AP2 genes have been reported to play a significant role in GA signaling pathways, which are involved in the growth and development of plants ( Magome et al., 2004 ; Xue et al., 2022 ). In a previous study, Zhang778 was proven to be caused by a mutation of the genes related to GA synthesis ( Zhang et al., 2020 ), which is consistent with the function of AP2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the nding in rice, GA plays a vital role in soybean plant height. A number of genes involved in GA biosynthesis or signaling pathways have been reported to regulate soybean height, such as GmDW1 (Dwarf Mutant 1) (Li et al 2018b), GmAP1s (Apetala1) (Chen et al 2020), and GmLHY (Late elongated hypocotyl) (Cheng et al 2019), ABI3/VP1 gene GmRAV (Xue et al 2022). It is well known that auxin promotes GA biosynthesis (Wolbang and Ross 2001;Ross et al 2000;Ross et al 2001).…”
Section: Shoot Heightmentioning
confidence: 99%